(untitled) (Islas, 2026)
Introduction: This article examines tourist service establishments along the Ayacucho–Apurímac corridor as sites of cultural differentiation in the southern Peruvian Andes. Specialized tourism literature has primarily emphasized economic analyses of these spaces or focused on festivals and gastronomy as distinctive tourism products, overlooking the potential of the everyday materiality of service environments as markers of territorial identity. Addressing this gap, the present study investigates the cultural differentiation strategies deployed by tourist service establishments and proposes, as a complementary methodological contribution, an Integrated Tourism Index (ITI) that translates these differences into a verifiable and replicable quantitative assessment. Methods: The study adopted a mixed-methods complementary design that combined direct observation of 24 establishments with surveys administered to 240 tourists (80 per city). Five dimensions were evaluated: physical attributes, service, human resources, location, and image. Statistical comparisons were conducted using the Chi-square (χ²) test and Cramér’s V coefficient, whose dimensionless nature allowed its use as a weighting factor in the construction of the ITI. Results: The Physical Attributes dimension showed differentiated values for the indicators Infrastructure Material and Presence of Waste Collection Facilities, for which negative responses predominated. In the Service and Human Resources dimensions, a statistically significant predominance of positive responses was observed. No significant differences were found among the tourist service establishments of the three cities in the Location and Image dimensions. Conclusions: The tourist service establishments along the corridor function as sites of active memory where built materiality, hospitality practices, and projected image express—or omit—the identities of their territories. Abancay displays a deliberate hybridization of Andean tradition and functional modernity; Andahuaylas exhibits a homogeneous modernity that dilutes local identity traits; and Huamanga presents unmanaged heterogeneity. The ITI provides a replicable and scalable metric with potential for institutionalization as a monitoring instrument for regional tourism and heritage authorities.